Promosi Aksara Ulu Sumatera Selatan Bagi Remaja Usia 12-18 Tahun Di Kota Palembang - Melda Tiana; Hestia Rachmat Nunciata Lubis; Husni Mubarat (UNIVERSITAS INDO GLOBAL MANDIRI, 2026)
Aksara Ulu is one of the cultural heritages of South Sumatra whose use has significantly declined, particularly among teenagers in Palembang who are more accustomed to the Latin alphabet. This phenomenon highlights the urgency of preservation through adaptive and relevant promotional strategies. This design project aims to produce educational promotional media that not only reintroduces Aksara Ulu but also raises awareness, stimulates curiosity, and broadens teenagers’ understanding of it as a cultural identity and a representation of local wisdom. The problem-solving approach applies visual communication strategies through the design thinking method with EDIPT stages, which include literature study, observation, interviews, and analysis of similar media. The promotional media are presented in interactive and varied forms, such as the Spin Ulu Script game, flashcards, erasable notebooks, animated letter jingles, infographic posters, foldable brochures, Instagram content, as well as merchandise including tote bags, t-shirts, water bottles, bamboo pens, and stickers. Visually, the design uses golden yellow combined with the Memphis style to create a cheerful, energetic, and attractive impression. The results show that integrating cultural values with visual design–based promotional strategies is effective in attracting teenagers’ interest in learning Aksara Ulu while strengthening their appreciation of it as a cultural identity of South Sumatra. Therefore, this project is expected to contribute to cultural preservation efforts through promotional media that are easy to understand, relevant, and aligned with the characteristics of the younger generation